Building MSME innovative capacity for healthier food supply: Learning from three MSME support mechanisms in Ethiopia - Mekonnen, Daniel A.; Nguyen, Trang; Teklehaimanot, Welday Hailu; Mengesha, Belay Terefe; Berkhout, Ezra (International Food Policy Research Institute, 2025)
Micro, small, and medium enterprises (MSMEs) constitute the vast majority of firms operating in the food system, particularly so in LMICs (Reardon et al., 2021). In sub-Saharan Africa (SSA), MSMEs are strongly involved in each stage of the food value chain; at the retail stage, between 70% and 100% of food is sold by MSMEs (Demmler, 2020). Harnessing the potential of food related MSMEs and informal businesses is suggested as one of the pathways to improve the availability, accessibility, and affordability of healthy foods, especially for lower income consumers (IFAD, 2021). This is because MSMEs have the potential to, among others, produce differentiated products that are highly local and traditional; adapt to high transaction costs; and innovate and offer complementary services such as inputs, information and logistics to small-scale producers in informal arrangements (Reardon et al., 2021; Liverpool-Tasie et al. 2020). Further, MSMEs are often located closer to the consumer, in villages and street markets, and can facilitate increased consumption of healthy foods while also contributing to the reduction of food loss and waste by engaging in food processing and other activities (Mekonnen et al., 2022). A study in Tanzania found that the proximity of informal vegetable vendors to a household was associated with a higher likelihood of vegetable purchases and lower consumption of carbohydrates (Ambikapathi et al., 2021). Another study in Kenya found strong associations between longer travel times to markets and lower diet quality for both vendors and consumers (Demmler et al., 2025). It is believed that MSMEs, often being close to consumers, can be agents of change for increasing consumption of healthy foods, if they possess sufficient innovative capacity.